Flipped classroom improves student learning outcome in Chinese pharmacy education: A systematic review and meta-analysis - Peng, Wei; Xiong, Ying; Wei, Jingwen; Chen, Xiuping; Huai, Wenying; He, Sike; Liu, Dan; Tian, Xiaoping; Tang, Songqi; Chen, Yunhui (Frontiers in Pharmacology, 2022)
Background: The application of flipped classroom (FC) pedagogy has recently become increasingly popular in Chinese pharmacy education. This study aimed to evaluate the effects of teaching with such a pedagogical approach by examining studies that compare the FC approach with the traditional lecture-based learning (LBL) module through a systematic review and meta-analysis. Methods: Seven databases, including the PubMed, EMBASE, Cochrane Library, China National Knowledge Infrastructure, Chinese Scientific Journals Database, Chinese Wanfang database, and China Biomedical Literature Database, were searched from the inception to June 30, 2021, to identify eligible articles of randomized controlled studies. The primary outcomes included the theoretical and experimental test scores, and the secondary outcomes were the results from questionnaires about the number of students who preferred the FC or endorsed its improving effects on their learning enthusiasm, self-learning ability, thinking skills, communication skills, and learning efficiency. The quantitative synthesis was conducted with Revman V.5.3 software following the Cochrane Reviewer’s Handbook guidelines and the PRISMA statement. Results: Eleven eligible studies published from 2017 to 2020 enrolling 1,200 students were included in this meta-analysis. The quantitative synthesis demonstrated that the FC module presented an overall more significant effectiveness over the LBL approach for Chinese pharmacy education in improving student academic performance as measured by theoretical test scores (SMD = 1.08, 95% CI: 0.60-1.56, P < 0.00001) and experimental test scores (MD = 6.62, 95% CI: 4.42-8.82, P < 0.00001). Further sub-group analysis revealed that the preferable effectiveness of FC was also evident in both theory-oriented (SMD = 0.77, 95% CI: 0.10-1.45, p < 0.00001) and experiments-oriented courses (MD = 6.52, 95% CI: 3.48-9.56, p < 0.00001) for both undergraduate (SMD = 0.84, 95% CI: 0.31-1.37, p < 0.00001) and three-year junior-college students (MD = 8.17, 95% CI: 6.44-9.89, p < 0.00001). Analysis on the questionnaire outcomes revealed that more respondents preferred for FC and endorsed its improvement effects on developing students’ learning enthusiasm, self-learning ability, thinking skills, communication skills, and learning efficiency. Conclusion: Current evidence suggests that FC pedagogical approach can effectively improve student learning outcomes and is applicable to Chinese pharmacy education.